2009
DOI: 10.1128/mcb.00200-09
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 2 Regulates Hepatic Lipid Metabolism

Abstract: In mammals, the liver integrates nutrient uptake and delivery of carbohydrates and lipids to peripheral tissues to control overall energy balance. Hepatocytes maintain metabolic homeostasis by coordinating gene expression programs in response to dietary and systemic signals. Hepatic tissue oxygenation is an important systemic signal that contributes to normal hepatocyte function as well as disease. Hypoxia-inducible factors 1 and 2 (HIF-1 and HIF-2, respectively) are oxygen-sensitive heterodimeric transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
284
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(312 citation statements)
references
References 53 publications
23
284
3
2
Order By: Relevance
“…Previous studies have consistently shown that developmental abnormalities caused by Vhl deficiency are partially reversible in double knockout animals with HIF deletion. 28,45,46 Nevertheless, pVHL exerts important HIFindependent effects on, for example, matrix metabolism and cytoskeletal function. 10,47 Our study also sheds some light on the role of the functional consequences of disturbed development of renin-producing cells, which were overall surprisingly minor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently shown that developmental abnormalities caused by Vhl deficiency are partially reversible in double knockout animals with HIF deletion. 28,45,46 Nevertheless, pVHL exerts important HIFindependent effects on, for example, matrix metabolism and cytoskeletal function. 10,47 Our study also sheds some light on the role of the functional consequences of disturbed development of renin-producing cells, which were overall surprisingly minor.…”
Section: Discussionmentioning
confidence: 99%
“…VHL encodes an E3 ubiquitin ligase ( 12,13 ) that targets HIF1α ( HIF1A ) and HIF2α ( EPAS1 ) for degradation ( 14,15 ). VHL loss in ccRCC results in constitutive activation of HIF1/2α and subsequent transactivation ( 16,17 ) of downstream genes regulating angiogenesis, glycolysis ( 18 ), lipogenesis ( 19,20 ), cell cycle ( 21 ), and antiapoptosis ( 22 ).…”
mentioning
confidence: 99%
“…HIF-2a shares 48% identity with HIF-1a and is an important transcriptional regulator of hypoxic responses, controlling a variety of processes including EPO synthesis, 13 lipid metabolism, 14 iron homeostasis, 15 vascular tumorigenesis, 16 and macrophage function. 17 Studies from our group 18,19 and others 20 have demonstrated that HIF-2a plays a key protective role in renal IRI, by preserving endothelial integrity and functions.…”
mentioning
confidence: 99%